1984
DOI: 10.1021/jo00193a031
|View full text |Cite
|
Sign up to set email alerts
|

Silicon in organic synthesis. 25. Thermolysis and desiliconation-alkylation of [1-(trimethylsilyl)cyclopropyl]ethylenes as a route to spirocyclic sesquiterpenes

Abstract: Three routes to [ [ 1-(trimethylsilyl)cyclopropyl]methylene]cyclohexanes and -2-cyclohexenes have been developed. The condensations of [ 1-(trimethyKiyl)cyclopropyl]lithium with cycloalkyl carboxaldehydes and of a-lithio selenides with 1-(trimethylsily1)cyclopropanecarboxaldehyde (10) are useful and complementary methods for gaining access to the methylenecycloalkanes. For more highly unsaturated systems, the methodology involving titanium-(0)-promoted coupling of 10 to cyclic a,@-unsaturated ketones is prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…It may be replaced by a proton, alkyl groups, or oxygen. 15 When treated with a source of fluoride, it may create a nucleophile that can react in high yield with proton sources, 16 alkyl iodides and triflates, 17 aldehydes, 18 and ketones, 19 as well as acylating groups such as acid chlorides 20 and carbon dioxide. 21 The unstable photoadducts were elaborated to more stable compounds in order to properly characterize them and, in particular, to verify the cis-syn-cis-relationship of the rings that should arise as a result of the endo selectivity (Scheme 4).…”
Section: Scheme 2 Reaction Progress Results In the Formation Of An Ismentioning
confidence: 99%
“…It may be replaced by a proton, alkyl groups, or oxygen. 15 When treated with a source of fluoride, it may create a nucleophile that can react in high yield with proton sources, 16 alkyl iodides and triflates, 17 aldehydes, 18 and ketones, 19 as well as acylating groups such as acid chlorides 20 and carbon dioxide. 21 The unstable photoadducts were elaborated to more stable compounds in order to properly characterize them and, in particular, to verify the cis-syn-cis-relationship of the rings that should arise as a result of the endo selectivity (Scheme 4).…”
Section: Scheme 2 Reaction Progress Results In the Formation Of An Ismentioning
confidence: 99%
“…25) 142 or α,β-unsaturated ketones (Eq. 26) 143 with monoaryl ketones or their corresponding aliphatic counterparts. The success of these reactions is also attributable to the sufficiently different redox potentials of two coupling components.…”
Section: Scheme 18mentioning
confidence: 99%
“…Renard et al [98] recently reported on the scope and limitations of intermolecular McMurry cross-coupling reaction between a benzylic ester and a hindered ketone. Using TiCl 3 (10 equiv)-LiAlH 4 (5 equiv)-Et 3 N (6 equiv) in THF at 70˚C and slow addition of both carbonyl compounds, a simple 1.2 excess of 2-adamantanone over tert-butyl- [73,99]. In this regard, stereoselective cross coupling of fluorinated-with nonfluorinated carbonyl compounds represents a potentially versatile approach to new chiral fluorine-containing diols.…”
Section: Mcmurry Coupling Reactionmentioning
confidence: 99%